EFFECT OF ADDING DIFFERENT LEVEL OF MARJORAM (Origanum vulgare) POWDER TO THE DIET IN DRESS PERCENTAGES AND NUMERAL OF CHARACTERISTICS CARCASSES BROILER - Zangana, Bushra S.; Al-Mashhadani, Salahuddin M. (Diyala Agricultural Sciences Journal, 2018)
The experiment aimed to investigate the effect of different levels of dietary Marjoram (Origanum vulgarae) powder supplementation in dress percentages and characteristics for carcass broiler reared for 42 days. 450 one old day Chicks of Ross 308 were divided randomly into five treatments (90 chicks per treatment) with three replicates (30 Chicks per replicate). Chicks were fed on starter and finisher rations with 23 and 20 % crude protein with energy 3027 and 3195.3 Kcal kg-1 respectively, in addition to the five levels of Marjoram powder 0, 0.5, 1, 1.5 and 2 kg per ton diet as T1, T2, T3, T4 and T5 respectively. Results showed there was significant priority (P<0.05) in thigh weight for T4, cold and hot carcass weight for T4 and T5 as well as thigh meat yield and dress percentages for T3 and T4 were observed as compared with T1. In conclusion supplementation of Marjoram (Origanum vulgarae) powder to broiler diet led to pronounced in dress percentage and numeral of carcass characteristics.